2021
DOI: 10.2166/wh.2021.186
|View full text |Cite
|
Sign up to set email alerts
|

The devil is in the details: emerging insights on the relevance of wastewater surveillance for SARS-CoV-2 to public health

Abstract: The severe health consequences and global spread of the COVID-19 pandemic have necessitated the rapid development of surveillance programs to inform public health responses. Efforts to support surveillance capacity have included an unprecedented global research response into the use of genetic signals of SARS-CoV-2 in wastewater following the initial demonstration of the virus' detectability in wastewater in early 2020. The confirmation of fecal shedding of SARS-CoV-2 from asymptomatic, infected and recovering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…In further support of research translation, we include an excellent review prepared by Hrudey & Conant (2022) drawing on their experience with the Canadian Water Network (CWN) Wastewater Coalition. Hrudey & Conant (2022) argue that appropriate interpretation of wastewater data for public health decision-makers requires an understanding of the importance of different knowns and unknowns.…”
Section: Wastewater Surveillancementioning
confidence: 99%
“…In further support of research translation, we include an excellent review prepared by Hrudey & Conant (2022) drawing on their experience with the Canadian Water Network (CWN) Wastewater Coalition. Hrudey & Conant (2022) argue that appropriate interpretation of wastewater data for public health decision-makers requires an understanding of the importance of different knowns and unknowns.…”
Section: Wastewater Surveillancementioning
confidence: 99%
“…In response to reports that the disease is more infectious and may be immune evading, flights were banned, and more measures were taken to control its spread in various regions of the world ( Chen et al 2021 , Gu et al 2021 ). Besides community-based monitoring of SARS-CoV-2 mutations, wastewater surveillance has been demonstrated to be a proper supplemental strategy ( Hrudey et al 2021 , Lee et al 2021 ). An epidemiological study retrospectively on routine surveillance data revealed that Omicron viruses might increase the risk of reinfection following primary infection ( Ferré et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater monitoring can help to address biases in analysis of clinical samples that are due to differences in test availability and willingness to undergo a clinical test. Moreover, increases in wastewater viral RNA levels can precede the results of clinical testing by several days or even longer when clinical testing is not readily available (Bibby et al, 2021;Hrudey and Conant, 2022), and thus wastewater analysis can provide early 1 warning signals of worsening epidemic situation or emergence of new variants of the virus in a particular area.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term studies have shown that the composition of viral RNA fragments in wastewater reflects qualitatively and quantitatively the breakdown of virus lineages circulating in the population of the catchment (Agrawal et al, 2022; Amman et al, 2022). Wastewater-based epidemiology (WBE) has recently emerged as a cost effective and scalable alternative to sequencing individual sample patients (Safford et al, 2022; Hrudey and Conant, 2022). Various PCR-based techniques can be used to estimate concentration of virus particles in wastewater to ascertain epidemiological trends.…”
Section: Introductionmentioning
confidence: 99%